IMPLEMENTASI MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN KEMAMPUAN MENULIS PANTUN - Shintari, Fur; Syam, Christanto; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is based on the low ability of students in writing. This can be evidenced from the value of students on average below 80, namely the minimum completeness criteria, students are less skilled in putting ideas or ideas into written form. The method used is descriptive method. The design used is Classroom Action Research (CAR). The technique used is indirect technique in the form of observation and documentary study. The tools used for data collectors are IPKG 1 and IPKG 2. The analysis technique used is descriptive qualitative. The results showed that the average score obtained by students in the first cycle was 52.47 or 39%, the total number of students completed was 12 people. Â Learning in the second cycle the average value of students isÂ 77.59 or 55%, the number of students who complete as many as 17 people. The average value of the first cycle also increased, namely 88.35 or 87%, the number of students who completed as many as 27 people. So, learning to write rhymes using the make a match model of cycles I, II, and Il has increased.Â Keywords: Make A Match, Poem, Writing